The Mysterious Rescue of adg1-1/tpt-2 – an Arabidopsis thaliana Double Mutant Impaired in Acclimation to High Light – by Exogenously Supplied Sugars - Heinrichs, Luisa; Schmitz, Jessica; Flügge, Ulf-Ingo; Häusler, Rainer E. (Frontiers in Plant Science, 2012)
An Arabidopsis thaliana double mutant (adg1-1/tpt-2) defective in the day- and night-path of photoassimilate export from the chloroplast due to a knockout in the triose phosphate/phosphate translocator (TPT; tpt-2) and a lack of starch (mutation in ADPglucose pyrophosphorylase [AGPase]; adg1-1) exhibits severe growth retardation, a decrease in the photosynthetic capacity and a high chlorophyll fluorescence (HCF) phenotype under high light conditions. These phenotypes could be rescued when the plants were grown on sucrose (Suc) or glucose (Glc). Here we address the question whether Glc-sensing hexokinase1 (HXK1) defective in the Glc insensitiv2 (gin2-1) mutant is involved in the sugar-dependent rescue of adg1-1/tpt-2. Triple mutants defective in the TPT, AGPase and HXK1 (adg1-1/tpt-2/gin2-1) were established as homozygous lines and grown together with Col-0 and Ler wild-type plants, gin2-1, the adg1-1/tpt-2 double mutant and the adg1-1/tpt-2/gpt2-1 triple mutant (additionally defective in the glucose 6-phosphate/phosphate translocator2 [GPT2]) on agar in the presence or absence of 50 mM of each Glc, Suc or fructose (Fru). The growth phenotype of the double mutant and both triple mutants could be rescued to a similar extent only by Glc and Suc, but not by Fru, All three sugars were capable of rescuing the HCF- and photosynthesis phenotype, irrespectively of the presence or absence of HXK1. Quantitative RT-PCR analyses of sugar responsive genes revealed that plastidial HXK (pHXK) was up-regulated in adg1-1/tpt-2 plants grown on sugars, but showed no response in adg1-1/tpt-2/gin2-1. It appears likely that soluble sugars are directly taken up by the chloroplasts and enter further metabolism, which consumes ATP and NADPH from the photosynthetic light reaction and thereby rescues the photosynthesis phenotype of the double mutant. The implication of sugar turnover and probably signaling inside the chloroplasts for the concept of retrograde signaling is discussed.